Legal and Professional Competence in the Preparation of Agrarians: Autonomy or Synergy? - Alekseevich Solopov, Vladimir; Aleksandrovich Verkhovtsev, Alexey; Vyacheslavovna Korotkova, Galina; Ivanovna Rudneva, Nina; Aleksandrovna Voropayeva, Victoria; Nikolaevna Cnernyaeva, Tatyana (International Journal of Engineering and Technology, 2018)
Modern Russia, being the agrarian-industrial country, sharply feels the need for highly qualified specialists of the agrarian sector. It is promoted by the new vector of the development directed to full import substitution of agricultural food. In these conditions, the inconsistency of the existing system of vocational education in Russia was revealed to the modern requirements of the domestic labor market. The professional community states the problem of staff shortage on the background of the annual numerous inflows of university graduates to the labor market. This situation has the right to claim that young specialists are often not ready for the independent professional activity according to their qualification.At the heart of many attempts to identify the primary sources of trouble in terms of staffing of the agricultural sector lies, first of all, the idea of over-theoretically preparing of the future specialists in universities and the substantive content of federal educational standards on which the universities are oriented in the context of the implementation of educational initiatives.It is assumed that the content of standards, verified and regulated by the ministry, determines the essence of the training of students of different educational levels and different areas of training. However, in the implementation in educational process of GEF of several â€œgenerationsâ€, the incompatibility of the formed competencies showed the real needs of the professional community. These facts became the primary reason for the annual approval of new requirements for higher education and, finally, focused on professional standards.The initial assumption is that the agrarian sector specialist should receive a practical-oriented education that forms professional and legal competence as the basis for future professional activity.Â Â